(untitled) (Journal of the College of Basic Education, 2025)
The aim of the research was to identify the effect of exercises similar to playing in improving motor agility and scoring in futsal for students, and to identify the effect of exercises similar to playing in improving motor agility and scoring in futsal for students. The researcher used the experimental method because it is suitable for the nature of the problem to be solved and to achieve the objectives and hypotheses of the research. The researcher also used the method of two equivalent groups (control and experimental with pre- and post-tests), as the two groups are completely equivalent in all their conditions except for the experimental variable that affects the experimental group. The research sample, which was selected randomly (lottery), included 67 third-year students in the Department of Physical Education and Sports Sciences - Al-Nusour University College The statistical package was used to reach the most important results, which led to the most important conclusions, including that the special exercises similar to sports performance contributed significantly to improving the movement agility of the participating students, which reflects the importance of focusing on these exercises within training programs, and a clear improvement in the accuracy and strength of scoring after implementing the designated exercises, which indicates their positive impact on developing the technical skills of the players. Among the most important recommendations of the research: 1. Applying exercises similar to playing to improve the movement agility and technical skills of the students such as scoring and designing special exercises that focus on improving scoring under pressure, so that they are similar to real situations in matches.